TIPS MENCARI IDE POKOK DENGAN MUDAH DALAM PARAGRAF BERBAHASA INGGRIS - Arifin, Riyadh (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Reading Comprehension is a skill or ability to understand what is read. In reading, sometimes students have difficulty understanding what the author of the text has said. Through this ability, a person can understand what the author means, then he builds his own meaning and understanding of the reading. For example, someone reads an article on the internet about the health benefits of drinking coconut water. From the article, the reader finds some texts that are difficult to understand. This could be new vocabulary or the meaning behind the text. Through reading comprehension, the reader can slowly understand it well and rewrite the article according to his understanding. As previously mentioned